EVALUASI EFISIENSI ENERGI PADA SISTEM GREEN BUILDING: PENDEKATAN BERBASIS DATA DAN SIMULASI - gufronramadhan; Anshori, Mohammad; Sulistiawan, Agus (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2025)
Green Building is a sustainable development concept with an environmentally friendly, responsible, and all-taking process (Widyawati, 2018). Green Building is designed to reduce the impact of the environmental environment on human health and nature, there are six aspects or categories of criteria in the evaluation of the Green Building assessment by GBCI (Green Building Council Indonesia) including appropriate land use, energy efficiency and conservation, Water conservation, Material Sources and Cycles, Air Quality and Space Comfort and Environmental Managemen. Energy use efficiency can achieve optimal energy levels according to the function of the building. The purpose of this study is to determine the level of energy efficiency in the Santoso Hardjosuwito building in Unugiri. The method used in this study is a quantitative. The results of this study indicate that the Santoso Hardjosuwito UNUGIRI building shows that the results of a detailed energy audit per month on light intensity of 15.87 kWh/m2. then electrical energy of 18 kWh/m2/Month. And for the air conditioning system of 14.05 kWh/m2/Month.